Consumers' Perceptions About Pharmaceutical Care Provided by Community Pharmacists in China in Relation to Over-the-Counter Drugs: A Qualitative Study - Hong Chen; Carolina Oi Lam Ung PhD; Peilian Chi PhD; Jihong Wu PhD; Daisheng Tang PhD; Hao Hu PhD (SAGE Publishing, 2018)
While patient-centered care is highly anticipated nowadays, investigation of consumers' perceptions and expectations about pharmacist's pharmaceutical care when providing over-the-counter (OTC) drugs is sparse. This article aimed to explore consumers' perceptions regarding the pharmaceutical care that community pharmacists provide in relation to OTC drugs. Semistructured interviews were conducted with consumers recruited (N = 97) in Yinchuan City, China. The 4 main themes that emerged were expectations on pharmaceutical care, attitude toward pharmacist's competence, experience of self-medication, and suggestions for improving pharmaceutical care. Most participants had high expectations on community pharmacists to recommend the right medicines, to advise them about the effective use of drug, to advise them about the safe use of drug, and to recommend economic drugs. However, their previous experiences at community pharmacy were far from satisfaction reportedly, leading to a general distrust in pharmacist's certification and qualification, knowledge, communication skills, and attitude. As a result, the participants turned to self-medication based on their personal experiences, their relatives' experiences, the information on drug label, and the information distributed in the mass media. Realizing the need to improve pharmaceutical care, the participants also made improvement suggestions specific to community pharmacist, community pharmacy, and the government.